2006
DOI: 10.1623/hysj.51.6.1065
|View full text |Cite
|
Sign up to set email alerts
|

On the quest for chaotic attractors in hydrological processes

Abstract: In the last two decades, several researchers have claimed to have discovered low-dimensional determinism in hydrological processes, such as rainfall and runoff, using methods of chaotic analysis. However, such results have been criticized by others. In an attempt to offer additional insights into this discussion, it is shown here that, in some cases, merely the careful application of concepts of dynamical systems, without doing any calculation, provides strong indications that hydrological processes cannot be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 25 publications
(31 reference statements)
0
28
0
Order By: Relevance
“…As most of these issues are also highly relevant to hydrologic time series, there have been criticisms on the correlation dimension estimates reported for hydrologic time series as well (e.g. Schertzer et al, 2002;Koutsoyiannis, 2006).…”
Section: Correlation Dimension Methodsmentioning
confidence: 99%
“…As most of these issues are also highly relevant to hydrologic time series, there have been criticisms on the correlation dimension estimates reported for hydrologic time series as well (e.g. Schertzer et al, 2002;Koutsoyiannis, 2006).…”
Section: Correlation Dimension Methodsmentioning
confidence: 99%
“…This situation is, of course, complicated by the fact that many hydrological systems exhibit strongly nonlinear behaviour and have unknown boundary and initial conditions. Together, this imposes principal limits on our ability to make (deterministic) predictions (Koutsoyiannis, 2010). So the important question that arises is 2.2 How can we cope with underdetermination and reduce explanatory pluralism in hydrology?…”
Section: Goals and Scope Of This Papermentioning
confidence: 99%
“…The theory of dynamical systems has since its beginnings in the 1950s (Forrester, 1968), developed into a well-established branch of science, that has been proven useful across a wide range of problems and systems (Strogatz, 1994), ranging from weather prediction (Lorenz, 1969), ecology (Hastings et al, 1993;Bossel, 1986) and hydrology (Koutsoyiannis, 2006) to geomorphology (Phillips, 1993) and coupled human-ecological systems (Bossel, 1999(Bossel, , 2007 among many others. The steps of dynamical system analysis (DSA) include identification of the system structure (border, components, and state variables) and of the laws governing its dynamics (i.e.…”
Section: Catchments As Complex Dynamical Systemsmentioning
confidence: 99%
“…Others attempted to demonstrate that irregular fluctuations observed in natural processes are au fond manifestations of underlying deterministic dynamics with low dimensionality, thus rendering probabilistic descriptions unnecessary. Some of the above views and recent developments are simply flawed because they make erroneous use of probability and statistics, which, remarkably, provide the tools for such analyses (Koutsoyiannis, 2006).…”
Section: What Is Randomness?mentioning
confidence: 99%
“…The limit of φ m (ε)/(−lnε) as ε tends to zero, which (according to de l'Hôpital's rule) is also equal to the limit of the slope d m (ε):=− φ m (ε)/ lnε, gives the dimension of the subspace of the m-dimensional space where the set of x m i lies. For small ε, d m (ε) cannot exceed m nor d. Application of a standard algorithm that implements this idea for increasing trial values of m (Grassberger and Procaccia, 1983;Koutsoyiannis, 2006) is demonstrated in Fig. 11, where it can be seen that d m does not exceed d=2, thus capturing the system dimensionality, which is 2.…”
Section: The Power Of Datamentioning
confidence: 99%